2009
DOI: 10.1007/s10803-009-0705-8
|View full text |Cite
|
Sign up to set email alerts
|

Vision in Children and Adolescents with Autistic Spectrum Disorder: Evidence for Reduced Convergence

Abstract: Evidence of atypical perception in individuals with ASD is mainly based on self report, parental questionnaires or psychophysical/cognitive paradigms. There have been relatively few attempts to establish whether binocular vision is enhanced, intact or abnormal in those with ASD. To address this, we screened visual function in 51 individuals with autistic spectrum disorder and 44 typically developing individuals by measuring visual acuity, stereoacuity, convergence, divergence, ocular motility, incidence of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 29 publications
7
54
0
Order By: Relevance
“…The evidence included in this review predominantly involves screening studies with only six studies employing a control group (Dammeyer 2014;Gal et al 2008;Hartshorne et al 2005;Hobson and Lee 2010;Hoevenaars-van den Boom et al 2009;Milne et al 2009). While the lack of control groups limits the robustness of the evidence, the screening studies provide quality information on the aetiology of a condition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence included in this review predominantly involves screening studies with only six studies employing a control group (Dammeyer 2014;Gal et al 2008;Hartshorne et al 2005;Hobson and Lee 2010;Hoevenaars-van den Boom et al 2009;Milne et al 2009). While the lack of control groups limits the robustness of the evidence, the screening studies provide quality information on the aetiology of a condition.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence relating to the prevalence of sight loss in people with ASD since 2000 is limited to seven studies (Black et al 2013;Ezegwui et al 2014;Ikeda et al 2013;Kabatas et al 2015;Kielinen et al 2004;Milne et al 2009;Mukaddes et al 2007). Table 1 details the quality of the evidence based on the criteria proposed in the Quality Assessment Tool for Quantitative Studies (Thomas et al 2004).…”
Section: The Prevalence Of Visual Impairment In People With Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Milne et al 17 reported that many vision aspects, including VA, are not affected in autism spectrum disorder in children. Our findings in children support their results.…”
Section: Discussionmentioning
confidence: 99%
“…However, data suggest that many aspects of vision, including VA, are unaffected in ASD. 17 Sven et al 18 found that people living with (PW) ASD did not have higher VA than either patients with schizophrenia or typically developing subjects. Tavassoli et al 19 analyzed the VA in adults with ASD and adult controls and found no significant differences between groups.…”
Section: Introductionmentioning
confidence: 99%